PENGGUNAAN JALA KABUT UNTUK STUDI POPULASI BURUNG GEREJA ERASIA (Passer montanus) DI KAMPUS IPB DRAMAGA: VARIASI JUMLAH TANGKAPAN DAN BOBOT TUBUH PADA MUSIM BERBEDA - Lina Kristina Dewi; Yeni Aryati Mulyani; Ani Mardiastuti; Fransisca Noni Tirtaningtyas (Media Konservasi, 2013)
The study of birds using mist nets in Indonesia is still small, but this method is good enough to see how the structure of a type of bird. A study of Eurasian Sparrow (Passer montanus) in IPB Darmaga Campus expected to provide information updates on community structure and see this type of variation in body weight in the different seasons. The study was conducted at the end of the rainy season and the beginning of the rainy season in 2012 with the installation of a total of 4514 net hours. During the study 125 individuals caught Eurasian Sparrow (71 individual at the beginning of the rainy season, 56 individuals at the end of the rainy season) and 12 individuals of which the individual retrap. No difference of body weight between the beginning of the rainy season and the end of the rainy season, but there are daily variations in body weight at the end of the rainy season between morning, afternoon and evening (df = 2 , Fvalue = 5.06 , P < 0.01). Individuals in different age classes juvenile are very real in the second season (χ2 = 7.80 ,df = 1 , P < 0.01). In the adult age class, the number of individuals in the second season was not significantly different (χ2 = 0.62 , df = 1 , P > 0.05). Keyword: body weight, structure of age, beginning of the rainy season, end of the rainy season